Sexual dysfunction associated with Sertraline and Mirtazapine : A comparative open label study (Journal of Psychiatrists' Association of Nepal, 2018)
Introduction: Antidepressants have become one of the most frequently prescribed drugs in the world. One of the most common side effects impairing the long term compliance for antidepressants is sexual dysfunction. Antidepressants like Sertraline have been associated with higher incidence of sexual dysfunction than Mirtazapine. However, there are studies which show that incidence of sexual dysfunction after use of Mirtazapine may be higher than previously expected. The aim of the study was to assess and compare the incidence of sexual dysfunction after therapy with Sertraline and Mirtazapine in a Nepali population.Material and Method: Patients needing antidepressant therapy but with minimal or no sexual dysfunction at baseline were randomly assigned to either Mirtazapine (n=54, 7.5-30 mg) or Sertraline (n=54, 25-100 mg). Various aspects of sexual functioning at baseline were measured with Change in Sexual Functioning Questionnaire (CSFQ) and the same were reassessed at 4 weeks.Results The incidence of sexual dysfunction seen in 42.9% patients in Sertraline group and 23.7% patients in Mirtazapine group. Sertraline showed significantly greater decline in Orgasm scores than Mirtazapine.Conclusion: Psychiatric referral rate and psychiatry morbidity was low. Sertraline caused significant decline in Orgasm aspect of sexual functioning. Although lesser in propensity, Mirtazapine is not free of adverse effect of sexual dysfunction. More studies are need to further confirm these findings.